Pulmonary alveolar proteinosis in children: An update on pathogenesis, clinical features and review of literature - Ahmad Hamed; Daniel Rosenbaum; Esther Cheng; Rizwana Popatia (Wolters Kluwer Medknow Publications, 2016)
Pulmonary alveolar Proteinosis (PAP) is a rare disease whereby the alveolar sacs are filled with a lipoproteinaceous material. The accumulation of this material hinders gas exchange, resulting in a variety of presentations involving all age groups. Symptoms range in severity from mild cough and dyspnea in most patients, to respiratory distress and failure to thrive in infants and young children. Depending on the etiology, PAP cases are classified as being hereditary, secondary, or autoimmune. Despite the different mechanisms underlying these, a unifying pathophysiological concept for PAP exists. Diagnosis is often difficult, and takes time to establish, given the vague nature ofthe presenting symptoms ofthis disease. High resolution computed tomography (HRCT) remains the preferred radiological diagnostic tool. Diagnosis is confirmed by lung biopsy and bronchoalveolar fluid lavage. Management encompasses whole lung lavage (WLL), exogenous GM-CSF therapy, supportive respiratory measures where necessary, and even lung transplant in some severe cases. Children affected with PAP remain a population with high mortality. Pediatric literature is scarce in comparison to PAP described in adults. This paper focuses on reviewing the pathophysiology in context to recent advances in molecular genetics, diagnosis, and management in children with this disease.